Neuromyelitis optica spectrum disorder coincident with renal clear cell carcinoma: A case report - Jin, Haiqiang (Medicine (Baltimore), 2019)
RATIONALE: Detection of aquaporin-4 (AQP4) antibody in cerebrospinal fluid (CSF) was not suggested for the diagnosis of neuromyelitis opica spectrum disorders (NMOSD). However, some patients with NMOSD have only AQP4 antibody positive in CSF but not in serum with unknown cause. Besides, it is rarely reported that NMOSD complicated with renal clear cell carcinoma. So, the relationship between AQP4-Ab, NMOSD and malignant tumors warrants an investigation. PATIENTS CONCERNS: A 31-year-old female presented in our hospital with chief complaints of urinary retention and weakness in bilateral lower extremities for more than 10 days. DIAGNOSES: The patient was diagnosed as NMOSD by neuroimaging and laboratory examination, with AQP4 antibody positive only in CSF. Besides, asymptomatic clear cell carcinoma was also found in left kidney. INTERVENTIONS: The patient underwent 2-month immunosuppressive therapy for NMOSD at first, including intravenous administration of immunoglobulin (IVIG) and methylprednisone, with oral drugs of predisone and tacrolimus. After that, Partial nephrectomy of left kidney was performed. OUTCOMES: The patient demonstrated almost complete remission for NMOSD after immunosuppressive therapy, and the renal tumor was cured by partial nephrectomy. LESSON: This case indicates that neuromyelitis optica (NMO)-IgG positive only in CSF could have potential association with the etiology of NMOSD, and renal clear cell carcinoma could be found complicated with NMOSD coincidently. Besides, it is necessary to examine NMO-IgG in CSF for patients suspicious with NMOSD, even when the serum test is negative, especially for those with complicated malignant tumors.